Pregnancy Outcomes in Patients With Adult-Onset Still's Disease: A Cohort Study From China - Wang, Zhihong; Chi, Huihui; Feng, Tienan; Du, Qinwen; Zeng, Ting; Teng, Jialin; Liu, Honglei; Cheng, Xiaobing; Ye, Junna; Shi, Hui; Sun, Yue; Hu, Qiongyi; et al. (Frontiers in Medicine, 2020)
Abstract Objective: Adult-onset Still’s disease (AOSD) is an autoinflammatory disease with a higher prevalence rate in young females. The purpose of this study is to investigate whether AOSD has an adverse impact on pregnancy outcomes, or conversely exacerbated by pregnancy. Methods: The outcomes of 191 pregnancies were evaluated in 86 female patients with AOSD. The generalized linear mixed model and propensity score matching method were conducted to evaluate the influence of AOSD on pregnancy outcomes. A dependent sample sign test was applied to assess the impact of pregnancy on the relapse of AOSD. Results: The results showed that the post-AOSD group had a lower proportion of normal delivery (25.0% vs 52.4%, p = 0.036) and a higher proportion of spontaneous abortion (STA) (18.8% vs 0.6%, p = 0.002) compared with the pre-AOSD group. Moreover, pregnancy after being diagnosed with AOSD was a significant high risk factor of STA (adjusted OR = 4.577, 95% CI: 4.166 to 845.119; p = 0.003). Disease flare upon conception was observed in 1 of 16 post-AOSD pregnancies (p = 1.000). There were 11 patients with new-onset AOSD during gestation or postpartum, among which 5 (45.4%) evolved into the polycyclic course. Conclusions: AOSD patients might suffer from a higher risk of STA, however, pregnancy might not be related with the exacerbation of diagnosed AOSD. New-onset AOSD during gestation or postpartum tend to evolve into the polycyclic course.